Maintenance management of GBI rated residential buildings / Nur Amira Adnan - Adnan, Nur Amira (Faculty of Architecture, Planning and Surveying, 2015)
The purpose of this research is to study and improve the maintenance management of GBI rated residential buildings. This study highlights the existing maintenance management systems existed in the residential buildings. The definition and issues of management, green building index, regulations and guidelines are emphasizing in chapter 2. Plus, there are three types of research methods used are indicated in chapter 3. Moreover, three case studies of maintenance management of green building index in residential buildings are executed to observe whether the user are satisfied with the maintenance management and whether it is complied with building regulations and requirements by using questionnaire. Besides, questionnaires are deliberated and executes in order to find out the problems exist on managing the residential buildings and to discover the dissatisfaction of the user. It can be concluded that the users of Ken Bangsar are more satisfied with the maintenance management. The least satisfied users are from Saville Serviced Apartment. Although most of the residents do not have the knowledge of Green Building Index and its requirements, but some of them, the highest rate is from Ken Bangsar, acknowledge the meaning and requirements of Green Building Index. Some recommendation collected through studies to improve the maintenance management is for the user to gain knowledge on green building index. Residential buildings that have the title of GBI should also be complied with the standard of green building. Finally, the conclusion and recommendations will be done based on the analysis for the case studies, checklist and questionnaire.